2015
DOI: 10.1016/s1473-3099(15)70093-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel outbreak enterovirus D68 strain associated with acute flaccid myelitis cases in the USA (2012–14): a retrospective cohort study

Abstract: SUMMARY Background Enterovirus D68 (EV-D68) is implicated in a widespread 2014 outbreak of severe respiratory illness across the United States, and has also been sporadically reported in patients with acute flaccid myelitis (AFM). The association between EV-D68 infection and AFM remains unclear. Methods Here we report metagenomic and molecular epidemiological analyses of 25 AFM cases in California and Colorado from 2012−2014. Findings EV-D68 was detected in respiratory secretions from 7 of 11 (64%) patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
415
7
10

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 354 publications
(468 citation statements)
references
References 29 publications
26
415
7
10
Order By: Relevance
“…Rather than report as little as a single sequence read within a pool as evidence of viral presence, we established a percent of reads threshold to account for 'leakage' observed when multiple samples (here pools tagged with different barcodes) are sequenced on the same flow cell using Illumina technology. This phenomenon has been observed in our laboratory (data not shown) and by others (Greninger et al, 2015;Quail et al, 2014), and may occur due to cross-contamination during sample preparation and/or misclassification due to acquiring a barcode from another sample during bridge PCR to generate DNA clusters on the same Illumina flow cell. In order to establish a stringent threshold criterion for viral detection, we took advantage of the presence of known HIV-seropositive samples included in nine plasma pools.…”
Section: à5supporting
confidence: 74%
“…Rather than report as little as a single sequence read within a pool as evidence of viral presence, we established a percent of reads threshold to account for 'leakage' observed when multiple samples (here pools tagged with different barcodes) are sequenced on the same flow cell using Illumina technology. This phenomenon has been observed in our laboratory (data not shown) and by others (Greninger et al, 2015;Quail et al, 2014), and may occur due to cross-contamination during sample preparation and/or misclassification due to acquiring a barcode from another sample during bridge PCR to generate DNA clusters on the same Illumina flow cell. In order to establish a stringent threshold criterion for viral detection, we took advantage of the presence of known HIV-seropositive samples included in nine plasma pools.…”
Section: à5supporting
confidence: 74%
“…EV-D68 infections mostly cause mild respiratory disease but can also result in severe bronchiolitis or pneumonia, especially among children (4,5). In 2014, a nationwide EV-D68 outbreak in the United States was associated with severe respiratory disease and a cluster of acute flaccid myelitis and cranial nerve dysfunction in children, implicating EV-D68 as an emerging public health threat (8,9).…”
mentioning
confidence: 99%
“…One study undertaken in Finland addressed this question, reporting high titres of neutralizing responses to EV-D68 in 80 % of the studied individuals [168]. However, neutralization responses in this study were addressed against the prototype EV-D68 Fermon strain, which is antigenically very different from the currently circulating EV-D68 strains [91,167]. Therefore, neither EV-D68 antigenicity, nor the population protection levels are understood well at the moment.…”
Section: Neutralization Of Enterovirus 68mentioning
confidence: 89%
“…Furthermore, EV-D68 has also been detected in four cases of AFP in Canada, two in Norway and one in France [87,89,90]. A recent retrospective study identified EV-D68 in respiratory secretions from 12 of 25 (48 %) patients with sporadic paralysis, strengthening the EV-D68 link to CNS disease [91]. Interestingly, all the EV-D68 strains identified in association with paralytic disease formed a distinct genetic cluster, suggesting the emergence of a novel clade and ongoing evolution of this virus [92].…”
Section: Enterovirus 68mentioning
confidence: 96%